História da Escola Rural Santa Tereza (Uberlândia/MG, 1934 a 1953) - Silveira, Tânia Cristina da (2008)
The subject of this research is about the history of the School Santa Tereza, an educational institution in Santa Tereza Farm, located in the city of Uberlandia (District of the City), between the years 1934 and 1953, when the majority of the population was living in rural area. The central problematic question that I tried to respond from this issue concerns the role played for this school in provide schooling for their students. The general purpose of the research was to (re)construct the history of this educational institution and grasp some aspects of school culture that permeated the school of the municipality of Uberlandia in that period. Specific purposes were: the context of rural education in Uberlandia, as well as in Minas Gerais and in the country; scrutinize the relationship between this education and the local, state and national society; understand the interactions between school culture in that institution under space focus and the elements that make up the culture through the universe where it installs a rural school; and finally, ask about the representation of backwardness of the rural universe constructed and appropriated for urban society. To meet these goals, the following sources were consulted: bibliography literature; newspapers and magazines; minutes and reports of inspection; registration books; daily class schedules and a notebook of a student of that school. The oral interviews with former students, former teachers and other people involved in the process in general were also employed as a source. The results of investigation indicate that rural schools of Uberlandia city in the period under study have a considerable quantitative growth. This fact was related to political interests, and to fight delay and lack of civility as terms recommended to rural areas. The traditional foundations of education taught in these schools improved the situation of the municipal school concerning illiterate rate compared with the reality of Minas Gerais and Brazil. Thus, the rural space is formed as a place of school, but characterized by little investment of the municipal government concerning the material and human resources. In this context the Municipal Rural School Santa Tereza fulfilled the role of literacy only, without, however neglecting the principles of moral and patriotic values. But its educational practices were distant from the inter-relationship school/life recommended by State legislation, since the school activities tended to idealize the urban area of the city of Uberlandia showing their physical and aesthetic development, to the detriment of peasant reality, practice come of positive representations of the first rather than last. This antagonism between rural/urban, in which the first would be linked to the perception of tradition, customs and human nature, while the second, the development and progress are representations of the European vision of reality stressed from changes with the modernity, which is spread through a large part of the American continent, particularly in Brazil. The consequences of this dichotomy for the rural school and in particular for the Rural School Santa Tereza increase the speech of comparison between rural schools and urban schools.